The Struggle for Recognition. The relationship between Hegel and Hobbes in the Jena Writings - Siep, Ludwig; Rosanovich , Damián (Estudios de Filosofía, 2011)
This is a study of the relationship between the hobbesian thought and the political philosophy of Hegel in the Jena writings. Particularly, starting with the connection between the ´war of all against all in the hobbesian State of Nature, and the Struggle for Recognition in Hegel, both theories are confronted, in order to weigh and evaluate to what extent is it possible to find in Hobbes´ work a precedent of central philosophical cores of young Hegel’s thought (e. g. State as realization of Ethical Life, the Struggle for Recognition, the Constitution of Intersubjectivity).